The formation peculiarities of the protein spectrum of blood plasma in mammals during the neonatal period - Melnychuck, D. O.; Grуshchenko, V.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
In the calves that are 36 hours old, the qualitative and quantitative changes of the blood plasma proteins, which are caused by the metabolic restructuring in tissues and by the absorption of the colostrum native proteins, in connection with the adaptation of newborn mammals to the extrauterine existence in the new environment, are elicited.